Fragmentos das trajetórias de vida de professores de educação física: aproximações da atuação com a pessoa com deficiência - Ramos, Jorge Marcos (2022)
The construction of the social imaginary has as its background the Eurocentric conception, in which the colonization project inserted the concept of inferiority in our culture, in which exploitation, violence and submission reverberate today. The objective of this research was to investigate the fragments of the life trajectory of physical education teachers and their possible contribution to the development of relationships and activities with students with disabilities. The aforementioned study was of a qualitative type, using Discursive Textual Analysis to analyze the information, based on phenomenological-hermeneutic procedures in order to produce new understandings about the narrated phenomena. The training courses of the participants prioritized technical training focused mainly on sports, reinforcing what they practiced and which served as a criterion for choosing that course. It is the role of the University to prepare the future Physical Education Teacher for the inclusion process with quality, after all, in the real school, the teacher has to deal with the student with a disability, being adequately equipped and prepared to provide him with the best participation. The lack of practical training and information regarding students with disabilities were pointed out by the participants as the biggest problems in relation to the possible adaptations to be made in their class, since the search for information regarding these students occurred from the needs they experienced. by the professionals themselves, in the day-to-day of their actions, not constituting a direct proposition of the Department of Education, nor of the Training Institutions, with the objective of better qualifying the referred professional to carry out their classes. There are several gaps that contribute to excluding attitudes, the values defended and propagated by society, the constitution of the school environment as part of this society, the personal values of this teacher that were forged by this society and strengthened by the school space, the family life, in the which there is no appreciation of differences, and Higher Education that often reinforces the pseudo-truths of its students. Based on the participants' reports, it was possible to verify that the early contact with the person with disabilities, as well as the appreciation and respect for differences influenced the development of actions for the student with disabilities, even though the aforementioned higher course through which the participants spent little contributed to the development of actions related to the attendance of students with disabilities in regular classes. From this work, it is concluded that multidisciplinary research is necessary to present a possible portrait of the different voices that constitute the school environment. Equally, an in-depth reflection on what to do at school is needed so that something, if not perfectly fair, at least is equitable in terms of educational opportunities for people with disabilities.(AU)